Adsorption behavior of modified Iron stick yam skin with Polyethyleneimine as a potential biosorbent for the removal of anionic dyes in single and ternary systems at low temperature. (December 2016) - Zhang, Yan-zhuo; Li, Jun; Zhao, Jing; Bian, Wei; Li, Yun; Wang, Xiu-jie
Highlights: We introduced both a new application of ISY@PEI for mixed dye treatments. The adsorption process was carried out in low temperature (5–15 °C) condition. The adsorption followed the pseudo second order model and Langmuir model. The characters of ISY@PEI were determined by SEM, EDS, FT-IR, BET and BJH. Abstract: The skin of Iron stick yam (ISY) was modified with Polyethyleneimine (ISY@PEI) and evaluated for use as a potential biosorbent to remove the anionic dyes Sunset yellow (SY), Lemon yellow (LY), and Carmine (CM) from wastewater under low temperature conditions (5–15 °C) in single and ternary dye systems. Both in the single and ternary systems, experimental data showed that adsorption capacity reached the highest value at 5 °C, and adsorption capacity decreased when the temperature increased (10–50 °C). The equilibrium data fitted very well to the Langmuir model and the extended Langmuir isotherm, for the single and ternary systems, respectively. The maximum adsorption capability was 138.92, 476.31, and 500.13 mg/g for LY, SY, and CM, respectively, in a single system and 36.63, 303.31, and 294.12 mg/g for LY, SY, and CM, respectively, in a ternary system. The adsorption followed pseudo-second-order kinetics. The thermodynamic parameters indicated that it was a spontaneous and exothermic process.